Internal preconditions of civilized conflict in Ukraine - Skvorets, Volodymyr (Skhid, 2015)
The objective factors that weakened the unity of the social organism of Ukraine were the background of the conflict in eastern Ukraine. Among them one should mention the historical and cultural heritage, based on civilizational characteristics of the region; the impact of globalization on international legal status of Ukraine characterized by the loss of its subjectivity and becoming an object of manipulation of the leading countries of the world; Ukraine ceased to express national and general public interests; neoliberal reforms led to the formation of the oligarchic regime in the country, while Ukrainian people turned into an "endangered nation"; socio-economic and socio-political changes in Ukraine show that society does not function as a whole any more but has broken into rivalling segments. Among the subjective factors that contributed to the formation of the conflict in Ukraine one should mention the following: all Ukrainian Presidents represented the group interests rather than national ones; the regional elite of Donbass sought to control other regions of the country, but due to Euromaidan they faced the threat of losing influence even in Donbass; armed separatists in Donbass are supported by some part of the region's population.